Mercury intracellular partitioning and chelation in a salt marsh plant, Halimione portulacoides (L.) Aellen: strategies underlying tolerance in environmental exposure - Válega, M (2009)
In the presence of metal stress, plants can resort to a series of tolerance mechanisms. Therefore field studies should be undertaken in order to evaluate the real role of these mechanisms in stress coping. The aim of this paper was to clarify the biochemical processes behind mercury tolerance in Halimione portulacoides (L.) Aellen (Caryophyllales: Chenopodiaceae) collected in a mercury contaminated salt marsh. Different fractions of mercury were separated: buffer-soluble (mainly cytosolic) and insoluble mercury (mainly associated with membranes and cell walls). The amounts in each fraction of metal were compared and related to metal distribution within plant organs. Protein-mercury complexes were isolated and analysed for their thiol content in order to assess wether the tolerance of this salt marsh plant was associated with the induction of metal chelation by phytochelatins. Overall, the mercury tolerance strategies of the plant are likely to involve root cell wall immobilization as a major mechanism of metal resistance, rather than metal chelation in the cytosolic fraction. Nevertheless, phytochelatins were demonstrated to chelate mercury under environmental exposure.